2023
DOI: 10.1590/1678-4324-2023220530
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature on Physicochemical and Microbiological Aspects of Serrano Artisanal Cheese Ripening

Abstract: The serrano artisanal cheese (SAC) is a traditional raw milk dairy produced in southern Brazil. The maturation temperature plays a crucial role regarding the cheeses' microbiological and physicochemical features and has been underexplored when it comes to unpasteurized milk dairy in Brazil. The objective of the present work is to evaluate the effect of ripening temperature on foodborne bacteria (total and thermotolerant coliforms, positive coagulase Staphylococcus and the production of its enterotoxin, Listeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, in most studies, Salmonella sp. [ 12 , 15 , 18 , 28 , 33 , 35 , 36 , 48 , 49 ] and L. monocytogenes [ 10 , 13 , 18 , 33 , 36 , 40 , 48 , 49 ] were absent in the various kinds of artisanal cheese surveyed. It is worth noting, though, that Allaion et al [ 34 ] detected 8 positive samples (out of 100) for Salmonella by PCR, but only one was confirmed by the culture-dependent method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in most studies, Salmonella sp. [ 12 , 15 , 18 , 28 , 33 , 35 , 36 , 48 , 49 ] and L. monocytogenes [ 10 , 13 , 18 , 33 , 36 , 40 , 48 , 49 ] were absent in the various kinds of artisanal cheese surveyed. It is worth noting, though, that Allaion et al [ 34 ] detected 8 positive samples (out of 100) for Salmonella by PCR, but only one was confirmed by the culture-dependent method.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the Serrano cheese produced in Santa Catarina state, two of the studies in the reviewed literature [ 15 , 41 ] demonstrated that 60 days of ripening may not be enough to meet the legal parameters since L. monocytogenes was present at 35 [ 41 ] and 60 days [ 15 ] of ripening. However, for Serrano cheese produced in Rio Grande do Sul state, Souza et al [ 68 ], Pretto et al [ 48 ], and Ströher et al [ 49 ] indicated a minimum ripening time ranging from 30 to 33 days, which is a much shorter ripening period that can still reach acceptable microbiological levels than those required by Normative Instruction SEAGRI N° 7 [ 63 ]. It is important to highlight that Ströher et al [ 49 ] demonstrated that the refrigerated temperature (5 °C) determined by IN 7/2014 is not adequate for ripening this type of cheese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation